THE IMPACT OF AGRICULTURAL PRACTICES ON GROUNDWATER QUALITY: A CRITICAL STUDY BASED ON NAVITHANVELI DS DIVISION IN AMPARA DISTRICT IN SRI LANKA - K, Nijamir; MIM, Kaleel (International Journal of Research -GRANTHAALAYAH, 2017)
This study was proceeded to identify the groundwater contamination based on the primary and secondary objectives. The primary objective is “identifying the groundwater contamination by the utilization of agro-chemicals, and the secondary objectives are “finding out Nitrate and Phosphate concentration to identify the Groundwater quality depletion by the chemical testing, identifying adverse agricultural practices and to make awareness among agro-chemical users by inducing traditional agricultural practices and recommend favorable solutions to the groundwater oriented problems in study area. For this study five parameters such as NO3, PO4, EC, pH and Turbidity were analyzed. All the parameters varied from wet season to dry season. Particularly, NO3 and PO4 concentration has deviated from both seasons. The conclusion of the study is that the application of the agrochemicals has impacted on the groundwater quality drastically.